Analysis of the Influence of Labor Union Functions on Employee Job Satisfaction and Work Motivation - Niki Etruly; Visca Erna Ardiyanti Putri; Juliasari Prasetya (Library of Sultan Agung Islamic University, 2026)
This research aims to determine the influence of the function of trade unions on the job satisfaction and motivation of PT employees. PGLSMID. Quantitative was the method chosen to be used in this research. PT employees. PGLSMID was used as the population and sample in the study with a sample size of 60 respondents. Data was collected using a questionnaire and then analyzed using multiple linear regression tests in the form of validity and reliability tests, normality tests, multicollinearity tests, heterodasticity tests and hypothesis tests. The results obtained in this research are that there is a simultaneous influence between the roles of the CLA makers and the trade unions in solving industrial problems; Trade unions have an influence in creating a harmonious, dynamic and fair relationship towards job satisfaction, there is a simultaneous influence between the role of the CLA maker and the trade union organization in resolving industrial problems; the influence of trade unions in creating harmonious, dynamic and fair relationships on the work motivation of PT employees. PGLSMID.